PENGARUH KOMPETENSI DAN KOMITMEN TERHADAP KINERJA GURU SMA NEGERI 1 BUNUT PELALAWAN - Suriyani, Evi; Hendriani, Susi; Amsal, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of the competence and commitment of the teacher in SMA Negeri 1 Bunut, Pelalawan, RIAU. The population of this study are all teachers of SMAN 1 Bunut which amounts to 44 people. The sampling technique using the method of taking the census respondents, where the number of samples taken are all teachers at SMA Negeri 1 Bunut . Pelalawan, RIAU. Data were analyzed using multiple linear regression analisis. These results indicatethat the competence and commitment of teachers significantly influence teacher performance SMA Negeri 1 Bunut. It can be seen from the two variablest value is greater than t table, respectively variables competence 3,003, variable commitment 2,390. Mean while, when these two variables simultaneously on the performance theacers SMA Negeri 1 BUNUT, then both significant effect on the dependent variable. It can be seen from the value off count greater than the table value of 30,850 f >3.226. Of lineare quation scanbe known constants of 6.234. Regression coefficient for competence 0.368 and commitment 0.346. Based on the value of the regression coefficients hows the most dominant variable is the variabel competence of 0,368.Keywords: Competence, Commitment, Performance